The Effect of Country of Origin and Product Quality on Purchase Intention: Case of Huawei Smartphones - Arjuna Wiwaha; Hendri Budiyanto (International Journal of Digital Entrepreneurship and Business, 2021)
This study aimed to discuss and determine the influence of Country of Origin and Product Quality on Purchase Intention for Huawei Smartphones. The research was conducted in a smartphone retail company at PT. Erafone Artha Retailindo, a branch of Roxy Mas. The research method used is library research by literature studies, scientific journals, and reports. Field research was done by collecting data from research objects through observation, interviews, and questionnaires. The data was collected from 140 visitors, who had not purchased at the Erafone branch in Roxy Mas. The valid sample used in this study amounted to 100 people. To process and analyze the data, this research used SPSS version 25. Based on the results, Country of Origin and Product Quality have a positive and significant effect either partially or simultaneously by 64.4%, on Huawei Smartphone Purchase Intention; the remaining 35.6% is influenced by other factors not covered in this study.